The Level of Community Perception, Motivation, and Participation in Tourism Village Management (Case Study of Pamegarsari Tourism Village, Parung District, Bogor Regency) - Arihsyah Putra Zai; Endang Koestati Sri Harini Muntasib; Bambang Sulistyantara (Postgraduate, University of Mataram, 2025)
Pamegarsari Tourism Village, officially established and inaugurated in October 2021 by the Minister of State-Owned Enterprises (BUMN) alongside the Regent of Bogor Regency, is managed by the Village-Owned Enterprise (BUMDes) with the aim of improving community welfare and Village Original Income (PADes) through community participation. However, the management activities of the tourism village have not been implemented effectively. This is primarily because the BUMDes faces various issues, particularly the perceived low active participation of the community. This lack of participation is suspected to stem from the village's establishment and inauguration being based solely on the natural potential of Situ Lebak Wangi, without adequately considering local community perception and motivation towards future tourism village management. This study aims to analyze the level of community perception, motivation, and participation in the management of Pamegarsari Tourism Village, as well as to analyze the relationship between perception and motivation on community participation. The research employed a descriptive method with a qualitative approach. Data on community perception, motivation, and participation were gathered from in-depth interviews with 100 purposively selected respondents. This research data was analyzed using a Likert scale measurement and Spearman's rho correlation analysis to test the relationship between perception and motivation on community participation. The study results indicate that community perception is predominantly neutral (54%), with a significant portion also being negative (24%). Community motivation is largely low (74%), and participation is predominantly low (86%). Furthermore, there is a strong and significant relationship between perception and participation (r=0.684; p=0.000), and a very strong and significant relationship between motivation and participation (r=0.882; p=0.000). The predominantly negative perception and low motivation directly correlate with low levels of community participation, showing a negative correlation.